Juvenile Finnraccoons (Nyctereutes procyonoides ussuriensis) choose to allohuddle on the cage floor instead of resting on a platform - Koistinen, Tarja; Korhonen, Hannu T. (Elsevier, 2017)
Comfort around resting is one of the key factors affecting farm animal welfare. The aim of the present study is to document the resting preferences in the Finnraccoon (Nyctereutes procyonoides ussuriensis) with special attention to the use of a platform. Sixteen sister-pairs of Finnraccoons were housed in 1.2m2 cages furnished with a platform made of plastic-coated wire mesh, similar to the mesh on the cage floor. The sister pairs were assigned to two experimental groups. In one group, the housing conditions remained unchanged throughout the growing season from weaning in July to the end of the study in December. In the other group, the access to the platform was temporarily prevented for two weeks in two occasions, i.e. in early autumn (September) and late autumn (November/December). The behaviour of the Finnraccoons was video recorded for six times: before each removal of the platform, during each removal of the platform and after returning access to the platform. The Finnraccoons rested in 67–74% of the daily observations. Allohuddling on the cage floor was the most common type of resting (61–91% of total resting time), being at a high level especially during the night-time. Resting alone on the cage floor and resting on the platform accounted 9–20% and 2–23% of the total resting time, respectively. These resting places were used more during the daytime than night. Including also activity, the platform was used for 2–17% of the total time. Due to the generally low level of platform use, the temporary deprivation of the platform did not affect the resting behaviour, but after the access to the platform was returned, the Finnraccoons did not quite discover the platform once again. Resting and sitting behaviours increased while the autumn proceeded. In contrast, the general activity level, including interaction with the activity object (bone), social behaviour, maintenance (eating and drinking), locomotion and stereotypic behaviour decreased. The Finnraccoons showed a clear circadian activity rhythm adjusted by daylight and human activities on the farm. Activity, including stereotypic behaviour, peaked in the early morning/before feeding. The results show that Finnraccoons prefer allohuddling on the cage floor instead of resting on a platform at night-time, whereas at daytime no so clear preference for resting site is observed. The platform is used for resting and activity during the daytime, which indicates that it is used for surveillance of human activities on the farm. Availability of a platform may enhance the welfare of Finnraccoons through increased complexity of the cage, although it is not used much.
Keywords: deprivation; fur farming; resting; behaviour; welfare